Interleukin-1β and uric acid as potential second-trimester predictive biomarkers of preeclampsia - Keziban Dogan; Alev Kural; Yasin Oztoprak; Murat Dogan (Taylor & Francis Group, 2021)
Methods: The prospective study was conducted at the University Hospital from February 2020 to December 2020. The study population (n = 88) included women who later developed PE (n = 42), as well as women who were healthy at birth (n = 46) in the second trimester of pregnancy. Serum levels of CRP, IL-1β, uric acid, creatinine, AST, ALT, MPV, Hb, PC, vitamin D, Ca, and Mg were compared between the groups. Results: Serum IL-1β and uric acid levels were significantly higher in subjects who eventually developed PE compared with those who did not. Conclusions: IL-1β and uric acid may be a predictive markers for PE. Maternal serum IL-1β and uric acid levels in the second trimester of pregnancy may be a predictive markers for PE.